Characterization of glandular trichomes in four Origanum vulgare L. accessions influenced by light reduction - Shafiee-Hajiabad, Marzieh; Novak, Johannes; Honermeier, Bernd; Justus Liebig University Giessen (My University, 2015)
The effect of reduced light intensity (minus 26%) on trichomes characteristics and herb yield responses of three subspecies of Origanum vulgare (ssp. vulgare, ssp. hirtum (Link) letswaart and ssp. viride (Boiss.) Hayek) and a hybrid (ssp. viride (Boiss.) Hayek x O. majorana L.) was investigated. It was found that the genotypes showed different morphological characteristics which were significantly influenced by light reduction. Reduced light intensity decreased the total indumentum of the leaf as well as the density and size of capitate glandular trichomes and size of peltate glandular trichomes. It also decreased the theoretical volume of essential oil on one peltate glandular trichome as well as the total theoretical volume of essential oil on adaxial side of one leaf. The indumentum of all samples included non-glandular trichomes, peltate glandular trichomes and capitate glandular trichomes type I. Capitate glandular trichomes type II with low density were observed only on O. vulgare ssp. viride and on the hybrid. It can be suggested that the applied light reduction was a limiting factor for the growth of O. vulgare L. plants. Reduced light shifted the carbon allocation to increase plant surfaces and therefore resulted in reduction of trichomes density of O. vulgare L.
Keywords: ddc:630